1994
DOI: 10.1037/0021-9010.79.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Why software testing is sometimes ineffective: Two applied studies of positive test strategy.

Abstract: The term positive test strategy describes the tendency to test a hypothesis with test cases that confirm (i.e., aim to support) rather than disconfirm the hypothesis. Most demonstrations of this phenomenon have involved relatively abstract problems. The authors suggest that people use a positive test strategy in a more applied setting as well, that is, in computer software testing. In 2 experiments, they examined how Ss with varying expertise performed functional testing of software. There was substantial evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 28 publications
(53 reference statements)
4
41
1
Order By: Relevance
“…An accumulating body of research on clinical judgment also report existence of confirmatory behaviour [16], [17]. In their laboratory and field studies, Teasley et al also observed that experienced programmers/testers exhibit confirmatory behaviour as much as novices [18], [19]. Our previous findings within the context of software engineering were inline with all these above mentioned studies.…”
Section: Characteristics Of the Software Engineerssupporting
confidence: 80%
“…An accumulating body of research on clinical judgment also report existence of confirmatory behaviour [16], [17]. In their laboratory and field studies, Teasley et al also observed that experienced programmers/testers exhibit confirmatory behaviour as much as novices [18], [19]. Our previous findings within the context of software engineering were inline with all these above mentioned studies.…”
Section: Characteristics Of the Software Engineerssupporting
confidence: 80%
“…We have also used verbal protocol techniques: The goal of the verbal protocol studies is to identify how positive test bias occurs in naturalistic software testing. In the following sections, we will review our previous work involving naturalistic testing tasks [see Teasley, Leventhal, Mynatt and Rohlman, 1993;Mynatt, Mynatt, Rohlman and Leventhal, 1992]. In our review below, we will refer to Studies 1, 2, 3 and 4.…”
Section: Review Of Our Workmentioning
confidence: 98%
“…test cases) that are compatible with their hypotheses. Our participants are developers, and as we mentioned previously, there is a similarity between software testing and Wason's Rule Discovery Task [64]. Hence, developers with Ind elim/enum values lower than 1 are more likely to be inclined to select positive test cases to verify their code.…”
Section: Interactive Question Metricsmentioning
confidence: 99%
“…al. in [64], there is a similarity between Wason's Rule Discovery Task and functional testing. Since the interactive question is Wason's Rule Discovery Task itself, the hypotheses testing behavior of the developer gives us clues about the strategies employed by the developer to test his/her own code.…”
Section: Confirmation Bias Metricsmentioning
confidence: 99%
See 1 more Smart Citation